Developing a Digital Wellbeing Scale Instrument for High School Students: Rasch Model Analysis - Siti Rohimah; Eka Sakti Yudha; Ipah Saripah (Universitas PGRI Yogyakarta, 2026)
Digital wellbeing is an individual's subjective condition in managing the impact of digital technology in a balanced manner. This study developed a Digital Wellbeing Scale instrument for high school students and tested its validity and reliability using Rasch model analysis, filling a literature gap that has only been available at the university level. The instrument was tested on 236 high school students with validity results based on the criteria of Outfit MNSQ (0.5–1.5), ZSTD (-2.0–+2.0), and Pt Measure Corr (0.4–0.85), where all 48 items met the standard. The instrument's reliability was classified as good (Cronbach's alpha = 0.86), with a person reliability of 0.84 (good) and an item reliability of 0.99 (excellent). This instrument can be used by guidance and counseling teachers to map students' digital wellbeing profiles and design programs to prevent the negative impact of technology. This research contributes to achieving Sustainable Development Goals (SDGs), particularly SDG 3 (Good Health and Wellbeing) by promoting mental health and preventing digital addiction among adolescents, SDG 4 (Quality Education) by providing schools with evidence-based tools to support student development, and SDG 10 (Reduced Inequalities) by ensuring equitable access to digital wellbeing assessment across diverse student populations. Keywords: adolescent mental health, digital wellbeing, educational assessment, instrument, Rasch model, senior high school, student